Controlled study of cytolethal distending toxin-producing Escherichia coli infections in Bangladeshi children. - Albert, M J (1996)
The role of cytolethal distending toxin (CDT)-producing Escherichia coli, a newly described category of E. coli, in the causation of diarrhea was studied by screening E. coli isolates from 546 children < 5 years of age with diarrhea and 215 matched controls without diarrhea by using a specific DNA probe. Although CDT-positive E. coli strains were isolated from more children with diarrhea than from healthy controls (3.1 versus 0.93%), this difference did not reach statistical significance (P = 0.082). All CDT-positive strains also possessed the virulence factors of enteropathogenic E. coli or enteroaggregative E. coli isolates.